Effects of environmental modification on the diversity and positivity of anopheline mosquito aquatic habitats at Arjo-Dedessa irrigation development site, Southwest Ethiopia - Dawit Hawaria; Assalif Demissew; Solomon Kibret; Ming-Chieh Lee; Delenasaw Yewhalaw; Guiyun Yan (BMC, 2020)
Abstract Background Irrigated agriculture is key to increase agricultural productivity and ensure food security in Africa. However, unintended negative public health impacts (e.g. malaria) of such environmental modification have been a challenge. This study assessed the diversity and distribution of breeding habitats of malaria vector mosquitoes around Arjo-Dedessa irrigation development site in Southwest Ethiopia. Methods Anopheline mosquito larvae were surveyed from two agroecosystems, 'irrigated' and 'non-irrigated' areas during the dry (December 2017-February 2018) and wet (June 2018-August 2018) seasons. Mosquito habitat diversity and larval abundance were compared between the irrigated and non-irrigated areas. The association between anopheline mosquito larvae occurrence and environmental parameters was analysed using Pearson chi-square. Multiple logistic regression analysis was used to determine primary parameters that influence the occurrence of anopheline larvae. Results Overall, 319 aquatic habitats were surveyed during the study period. Around 60% (n = 152) of the habitats were positive for anopheline mosquito larvae, of which 63.8% (n = 97) and 36.2% (n = 55) were from irrigated and non-irrigated areas, respectively. The number of anopheline positive habitats was two-fold higher in irrigated than non-irrigated areas. Anopheline larval abundance in the irrigated area was 16.6% higher than the non-irrigated area. Pearson's chi-square analysis showed that season (χ 2 = 63.122, df = 1, P < 0.001), agroecosystem (being irrigated or non-irrigated) (χ 2 = 6.448, df = 1, P = 0.011), and turbidity (χ 2 = 7.296, df = 2, P = 0.025) had a significant association with larval anopheline occurrence. Conclusions The study showed a higher anopheline mosquito breeding habitat diversity, larval occurrence and abundance in the irrigated than non-irrigated areas in both dry and wet seasons. This indicates that irrigation development activities contribute to proliferation of suitable mosquito breeding habitats that could increase the risk of malaria transmission. Incorporating larval source management into routine malaria vector control strategies could help reduce mosquito population density and malaria transmission around irrigation schemes.